MODEL PEMBERITAAN KABAR BAIK MELALUI MEDIA DIGITAL - Febriyanti, Ruth; Didasgil, Yeremia; Sunarti, Yohana (JOURNAL of THEOLOGICAL STUDENTS, 2024)
Digital media helps believers share the gospel through animated images and short videos. Evangelism can be done anytime and anywhere, and can reach more souls. This study aims to find out how the Model of Reporting Good News Through Digital is Effective for STT Alfa Omega Semarang Students. The method used is descriptive qualitative method. Researchers get the result that the obstacles students face in preaching the Bible are quotas and networks. The media most often used in preaching the gospel are WhatsApp and Instagram.